Deformation due to inclined load in thermoelastic half-space with voids - Kumar, R.; Rani, L. (Archives of Mechanics, 2005)
The two-dimensional deformation of homogeneous, isotropic, thermoelastic half-space with voids as a result of inclined line load is investigated by applying the Laplace and Fourier transforms. The inclined load is assumed to be a linear combination of a normal load and a tangential load. The displacements, stresses, temperature distribution and change in volume fraction field so obtained in the physical domain are computed numerically. The variations of these quantities have been depicted graphically in the Lord-Shulman (L-S) theory and Green-Lindsay (G-L) theory for an insulated boundary.